1984
DOI: 10.1182/blood.v64.6.1179.1179
|View full text |Cite
|
Sign up to set email alerts
|

Therapeutic experience on 934 adults with idiopathic thrombocytopenic purpura: Multicentric Trial of the Cooperative Latin American group on Hemostasis and Thrombosis

Abstract: In order to analyze the usefulness of different types of treatment in relation to the interval since the onset of idiopathic thrombocytopenic purpura (ITP), a collaborative study of 934 adult patients was undertaken. Prednisone was administered to 818 patients, and 32% of them achieved prolonged complete remission (PCR). However, only 14% of patients who had ITP for more than six months achieved a prednisone- induced PCR (P less than .01). Splenectomy was done in 399 patients, and 65% of them achieved PCR; the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
25
1
3

Year Published

1987
1987
2018
2018

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 188 publications
(30 citation statements)
references
References 13 publications
1
25
1
3
Order By: Relevance
“…In the present study, the death rate from causes directly related to ITP or its treatment was 1AE6% with only one patient dying at presentation. This would be in keeping with the experience of others (Watson-Williams et al, 1958;Doan & Bouroncle, 1960;Thompson et al, 1972;JiJi et al, 1973;DiFino et al, 1980;Picozzi et al, 1980;Pizzuto & Ambriz, 1984;Cortelazzo et al, 1991;Portielje et al, 2001) where the reported incidence was 0-5%.…”
Section: Discussionsupporting
confidence: 84%
See 2 more Smart Citations
“…In the present study, the death rate from causes directly related to ITP or its treatment was 1AE6% with only one patient dying at presentation. This would be in keeping with the experience of others (Watson-Williams et al, 1958;Doan & Bouroncle, 1960;Thompson et al, 1972;JiJi et al, 1973;DiFino et al, 1980;Picozzi et al, 1980;Pizzuto & Ambriz, 1984;Cortelazzo et al, 1991;Portielje et al, 2001) where the reported incidence was 0-5%.…”
Section: Discussionsupporting
confidence: 84%
“…The total number of patients progressing to splenectomy was 12% (see Table III). This is lower than in the literature (28-88%, see Table VII) (Watson-Williams et al, 1958;Doan & Bouroncle, 1960;Thompson et al, 1972;JiJi et al, 1973;DiFino et al, 1980;Picozzi et al, 1980;Pizzuto & Ambriz, 1984;Jacobs & Wood, 1986;Cortelazzo et al, 1991;Portielje et al, 2001) and may reflect a more selected group of patients in other studies.…”
Section: Discussionmentioning
confidence: 54%
See 1 more Smart Citation
“…The response rate of azathioprine is higher than previous studies, which reported complete response rates of 20%-45%. [29][30][31] It may result from difference in case enrollment and definition of response. As the baseline conditions of these two treatment groups are not balanced in such a retrospective study, the outcome should not be compared with each other in an objective analysis.…”
Section: Discussionmentioning
confidence: 99%
“…The overall mortality rates in ITP have been estimated in more than a dozen studies, and they vary from 0.1% to as much as 5.0% (Table 1) (6,7). Mortality rates do increase with age, and age-adjusted bleeding risks estimated by meta-analysis are 0.004, 0.012, and 0.130 cases per patient-year for age groups younger than 40, 40-60, and older than 60 yr, respectively (8).…”
Section: Criteria For Treatmentmentioning
confidence: 99%